A Model of Community Defending Public Awareness Development in the Bandung City - Mursyid Setiawan; Cecep Darmawan (Journal of International Conference Proceedings (JICP), 2020)
The purpose of this study is to determine the model of fostering awareness of national defense for society in the Bandung city. The findings showed that the efforts to foster awareness of national defense for the society in Bandung used the pentahelix model which involved several elements, such as; government, academia, the business world, society, and media. Efforts to foster awareness of public defense were carried out through defending education and state training programs, then state defense action programs organized by Bandung National Unity and Politics Agency. The result of the process in fostering awareness of the defense of the state was the embedded values of the basic defense in every society. The implications of this research were each element incorporated in the pentahelix model continues to synergize and collaborate in shaping and fostering the awareness of the defense in the public state.